(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2022)
Building 2 is located on the Victor Levi Sasso Campus of the Universidad Tecnológica de Panamá and has a floor area of approximately 2,361 m2. Based on the inventory, it is estimated that Building 2 has an annual consumption of 1,237.16 MWh, which reflects an expenditure of approximately 188,889.70 per year. Of the 3 areas identified with potential energy savings in the building, alternatives have been presented for the lighting, air conditioning and renewable energy systems, achieving electrical savings of up to 62% and avoiding the emission of 146.01 tons of CO2 into the atmosphere per year